Extending the theory of planned behavior to explain halal entrepreneurial intention: evidence from SEM-PLS analysis - Utari Evy Cahyani; Ahmad Afandi; Rizal Ma’ruf Amidy Siregar (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2026)
This study examines the factors influencing students’ intentions to start a halal business at Perguruan Tinggi Keagamaan Islam Negeri (PTKIN) in Indonesia. It extends the Theory of Planned Behavior (TPB) by incorporating halal industry knowledge and awareness as additional determinants. Data from a survey of 300 PTKIN students were analyzed using PLS-SEM. The results show that knowledge of and strong awareness of the halal industry greatly and positively influence students' views on starting a business in the halal sector. Moreover, being entrepreneurial, feeling that others approve of entrepreneurship, and believing you can control your actions all had a positive and significant impact on the intention to start a halal business, with the belief in controlling your actions being the strongest influence. Halal entrepreneurial attitudes act as both complete and partial mediators between halal industry knowledge and awareness and the decision to start a business. The unique part of this study is the development of a TPB model grounded in halal values, highlighting the importance of knowledge and awareness of the halal industry in shaping entrepreneurial attitudes. It applies the model nationally within the underexplored PTKIN context and recommends strengthening halal entrepreneurship curricula and institutional support.